1998
DOI: 10.1046/j.1432-1327.1998.2520253.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural analysis of oligosaccharide‐alditols released by reductive β‐elimination from the jelly coats of the anuran Bufo arenarum

Abstract: Amphibian egg jelly coats are formed by components secreted along the oviduct. These secretion products overlay the oocytes as they are transported toward the cloaca. Mucin type glycoproteins are the major constituents of the egg jelly coats. In this study, the O-linked carbohydrate chains of the jelly coat surrounding the eggs of Bufo arenarum were released by alkaline borohydride treatment. Fractionation of the mixture of O-linked oligosaccharide-alditols was achieved by a combination of chromatographic tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 6 publications
2
20
0
Order By: Relevance
“…By comparison with the NMR spectrum of compound 100‐H, the strong downfield shift of Gal III H‐1 (Δδ = +0.173 p.p.m.) suggests the existence of the Fuc(α1,2)Gal(β1,3)[Fuc(α1,2)]Gal(β1,3) sequence, already observed in the oviducal mucin of Xenopus laevis [8], R. dalmatina [16] and Bufo arenarum [17]. The presence of such a sequence was confirmed by the set of Gal II H‐3 and H‐4 resonances observed at δ = 4.173 and 4.018 p.p.m., respectively, and the downfield shifts observed for Gal III H‐2 (Δδ = +0.067 p.p.m.)…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…By comparison with the NMR spectrum of compound 100‐H, the strong downfield shift of Gal III H‐1 (Δδ = +0.173 p.p.m.) suggests the existence of the Fuc(α1,2)Gal(β1,3)[Fuc(α1,2)]Gal(β1,3) sequence, already observed in the oviducal mucin of Xenopus laevis [8], R. dalmatina [16] and Bufo arenarum [17]. The presence of such a sequence was confirmed by the set of Gal II H‐3 and H‐4 resonances observed at δ = 4.173 and 4.018 p.p.m., respectively, and the downfield shifts observed for Gal III H‐2 (Δδ = +0.067 p.p.m.)…”
Section: Resultsmentioning
confidence: 93%
“…All the collected fractions were desalted by gel permeation on a Bio‐Gel P2 column (55 × 2 cm), and lyophilized [20]. The different steps of the purification are explained in detail in many previous papers [12–17].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…When compared to Bombina pachypus , which we studied previously (Scillitani et al, ), B. bufo and B. balearicus have a lower number of jelly layers, but a comparable number of glycan types as evidenced by lectin histochemistry. Similarly, a survey of the available literature about ECM composition in bufonid toads (Arranz et al, ; Coppin et al, ; Farias et al, ; Kawai and Anno, ; Morelle et al, ; Omata, ; Reddy and Seshadri, ) indicates that in the two species we studied there are the main residuals found in other species, such as galactose, N ‐acetylgalactosamine, N ‐acetylglucosamine, sialic acid, fucose, and mannose. Besides, patterns of lectin binding allow to discriminate the two species between them and could be even used as a tool for egg identification.…”
Section: Discussionmentioning
confidence: 52%
“…It has been suggested that N ‐linked glycans, in particular lactosamine chains, have a structural function, orientate regulatory molecules, and are involved in water retention (Scillitani et al, ). Anyway, lactosaminylated residuals in O ‐linked chains cannot be excluded, as their presence in egg jelly was reported (Coppin et al, ; Morelle et al, ). As lectin binding is observed with RCA‐1 but not with PNA, galactose in saccharidic chains is probably linked to N ‐acetylglucosamine, not to N ‐acetylgalactosamine.…”
Section: Discussionmentioning
confidence: 99%